Evaluation of a Model Comparative Drug Price Resource in Fostering Prescriber - Patient Engagement, Lowering Consumer Costs and Improving Adherence - Marcia Hams; Wells Wilkinson (University of Minnesota Libraries Publishing, 2014)
Type: Original Research